DEVELOPING PERSONA FOR USED CAR BUYERS IN INDONESIA - Rayhana Putri, Amalia
Indonesia used car market is predicted to register a CAGR of about 5.74% in 2027. As there may be a shift in buyer behaviors and an increase in the number of Indonesian used car players in the future, in order to remain competitive in the market, developing a buyer persona is one of the most essential solutions. A buyer persona is a profile that describes a business’ ideal customer. Most marketers are familiar with demographic segmentation, however, buyer persona takes it into another level. Buyer Persona could help businesses target the demographics deeper and help businesses to understand not only who their customer is but also how to talk to them. Currently, in Indonesia, persona development in the automotive industry is very limited, due to limited research and digital players in the market. There are approximately 50k auto dealers in Indonesia. However, some of them, mostly SMEs auto dealers, still have limited resources, especially to do some research about market conditions. Therefore, this research could be a reference for automotive businesses to understand customers' motivations. Herewith, businesses could create marketing materials that match customers’ preferences, desires, and needs. The data collection used in this study is by using quantitative and qualitative methods. Quantitative methods will be used for buyer persona development by using an online survey questionnaire. There are three variables that will be used in developing buyer persona for used car buyers, such as biographic information, users buying triggers, and consumer behaviors. Cluster analysis will be used to analyze the result of the survey questionnaire in developing the persona. After the persona is developed, then a qualitative method will be used to map the customer journey on the certain personas by using an in-depth interview. The survey was filled by 284 respondents who have ever bought a used car. According to the cluster analysis result, there are four persona developed, which are The Millennials, The Working Mum, The Busy Man, and The Entrepreneur. Each persona has their own journey in buying a used car. Every step of the journey map will generate customers’ emotions, which are positive and negative/pain points. In addition, the pain points from the journey mapping will be used for the recommendation actions.